2021
DOI: 10.1177/1534734619851700
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kiwifruit Therapeutics in the Treatment of Diabetic Foot Ulcer

Abstract: Diabetes mellitus is considered a silent disease with possible late chronic complications such as diabetic foot ulcer. This condition is managed by surgical debridement. To improve surgical outcome, some surgeons use proteolytic agents after surgery. Kiwifruit contains a type of proteolytic enzyme called actinidin that may play a role in the treatment of such complication. In the current study, we evaluate the role of kiwifruit extract in the treatment of diabetic foot ulcer. Eighteen diabetic foot ulcer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 20 publications
0
22
0
6
Order By: Relevance
“…In that regard, ultimate biological activities toward specific diseases could be approached to recommend dietetic therapy application. There are rare or no available publications about using kiwifruit as a gastro-protective agent despite efficient application in the treatment of diabetic foot ulcers [18,19]. Kiwifruit had higher total flavonoids, total chlorophyll, carotenoids, and vitamin C [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that regard, ultimate biological activities toward specific diseases could be approached to recommend dietetic therapy application. There are rare or no available publications about using kiwifruit as a gastro-protective agent despite efficient application in the treatment of diabetic foot ulcers [18,19]. Kiwifruit had higher total flavonoids, total chlorophyll, carotenoids, and vitamin C [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is no available information on the antiulcerogenic activity of SP and kiwifruit individually or in combination against peptic ulcers. However, even though the literature showed promising potentialities related to the use of SP and kiwifruit [18] separately, the gastroprotective potential of SP and kiwifruit both individually or in combination needs to be carefully investigated. Moreover, literature has mainly reviewed the antiulcerogenic efficiency of golden kiwifruit in Swiss albino mice [24], but the antiulcerogenic and gastroprotective potential of golden kiwifruit, their peels, and SP individually and/or in combination has not been studied so far, thus motivating this work.…”
Section: Introductionmentioning
confidence: 99%
“…Promising studies have been indicated that actinidin could be used for diabetes mellitus due to its ability to degrade α‐amylase [259] . Furthermore, the topical administration of kiwifruit for 4 weeks could heal diabetic ulcers in patients [260] . StSBTc‐3 is a cucumisin‐like protease obtained from Solanum tuberosum with the capacity to inhibit platelet aggregation without cytotoxic activity on human erythrocytes agent.…”
Section: Plant Protease Applicationsmentioning
confidence: 99%
“…[259] Furthermore, the topical administration of kiwifruit for 4 weeks could heal diabetic ulcers in patients. [260] StSBTc-3 is a cucumisin-like protease obtained from Solanum tuberosum with the capacity to inhibit platelet aggregation without cytotoxic activity on human erythrocytes agent. Therefore, StSBTc-3 shows potential to be used in the treatment of thromboembolic disorders such as strokes, pulmonary embolism, and deep vein thrombosis.…”
Section: Wrightia Tinctoriamentioning
confidence: 99%
“…O Diabetes Mellitus (DM) é uma doença crônica silenciosa de importância mundial e considerada um grave problema de saúde pública, por promover diversas complicações preocupantes, como o pé diabético (1) , que se caracteriza por uma úlcera nos membros inferiores agravada por uma infecção. O pé diabético se origina de problemas relacionados às diversas áreas suscetíveis da doença, como nervos, pele, vasos e sistema músculo esquelético dos pés (2) .…”
Section: Introductionunclassified